Modification of the existing maximum residue level for acequinocyl in sweet peppers/bell peppers. (4th March 2022) - ; Bellisai, Giulia; Bernasconi, Giovanni; Brancato, Alba; Cabrera, Luis Carrasco; Ferreira, Lucien; Giner, German; Greco, Luna; Jarrah, Samira; Leuschner, Renata; Magrans, Jose Oriol; Miron, Ileana; et al.
Abstract: In accordance with Article 6 of Regulation (EC) No 396/2005, the applicant Agro‐Kanesho submitted a request to the competent national authority in Germany to modify the existing maximum residue level (MRL) for the active substance acequinocyl in sweet peppers/bell peppers. The data submitted in support of the request were found to be sufficient to derive MRL proposal for peppers. Adequate analytical methods for enforcement are available to control the residues of acequinocyl in peppers at the validated limit of quantification (LOQ) of 0.01 mg/kg. Based on the risk assessment results, EFSA concluded that the short‐term and long‐term intake of residues resulting from the use of acequinocyl according to the reported agricultural practice is unlikely to present a risk to consumer health.